Intra- and inter-field compositional changes of oils from the Misoa B4 reservoir in the Ceuta Southeast Area (Lake Maracaibo, Venezuela). (1st March 2016) - Márquez, G.; Escobar, M.; Lorenzo, E.; Duno, L.; Esquinas, N.; Gallego, J.R.
Highlights: This work is an analysis of 35 oils from the Ceuta Southeast Area (NW Venezuela). They all fall into 5 families derived from 2 oil pulses from the La Luna source rock. Pyrolysis of asphaltenes confirmed that LG-62 oil represents biodegraded end-member. GC fingerprints and FTIR indices were used to assess Misoa B4 compartmentalization. Abstract: Here we analyzed oil samples from 35 wells in the Ceuta Southeast Area (Lake Maracaibo Basin, northwestern Venezuela) in order to evaluate lateral intra-reservoir continuity in the Misoa B4 unit. Biomarkers, isotopic signature, and also V and Ni were examined using gas chromatography–mass spectrometry (GC–MS), isotope ratio mass spectrometry (IRMS), and inductively-coupled plasma atomic emission spectroscopy (ICP-AES). Multivariate statistical analysis was also applied to obtain useful information from geochemical data. On the basis of the characterization of these samples, we conclude that they all fall into various oil families derived from two pulses of hydrocarbon generation, migration and accumulation from the calcareous La Luna source rock, deposited in an anoxic marine environment under reducing conditions. Thus, these oils are a mixture of an earlier biodegraded, less mature oil charge and a later fresh non-biodegraded oil recharge. In addition, we applied asphaltene pyrolysis to one (LG-62) of the three "anomalous" oils. The LG-62 sample was confirmed as an almost "pure" paleobiodegraded end-member, whereas the VLF-3020 oil was tentatively classified as the unaltered end-member oil-type. Finally, the GC fingerprints and Fourier Transform Infra Red (FTIR) spectroscopic indices of the oils were used to detect minor variations in composition that are indicative of reservoir compartmentalization.